Penggunaan Metode FDTD untuk Analisis Gelombang pada Struktur Berbasis Kartesian dan Silinder - Nabila Husna Shabrina; Hardi Nusantara; Achmad Munir (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2018)
In this paper, the comparison of wave characteristics between Cartesian and cylindrical coordinate system–based structures was analyzed using finite-difference time-domain (FDTD) method. The use of FDTD method wasconsidered due to its advantage in solving electromagnetics (EM) problems in wide spectrum of frequency and geometry shapes. The analysis was undertaken for three-dimensions (3D) Cartesian and cylindrical coordinate system–based structures with dimension of x = 600 mm, y = 300 mm, z = 1.200 mm, dan ???? = 600 mm, ???? =1 °, z = 1.200 mm, respectively. A transverse electric (TE) mode excitation of sine wave modulated Gaussian pulse with frequency of 1 GHz was applied for exciting both structures with the direction of propagation wave assumed in z–axis. Some scenarios were applied for both structures conditioned with free space, dielectric, and conductive medium. The attenuation rate obtained from three modelling scenarios in Cartesian coordinate system structures were 0.35 Np/m, 0.24 Np/m, and 0.62 Np/m, respectively. Meanwhile the attenuation rates for cylindrical coordinate system structure were 0.35 Np/m, 0.21 Np/m, and 0.40 Np/m. The simulation result for resonant frequency in Cartesian and cylindrical coordinate systemstructure conditioned with free space were 558.706 MHz and 498.466 MHz, respectively. The resonant frequency obtainedfrom simulation result in Cartesian and cylindrical coordinatesystem structure conditioned with dielectric medium was similar with the one from theoretical calculation in which the highesterror were 2.03% and 0.73%, respectively.